The Role of Brand Image and Trust in the Adoption of FinTech Digital Payment for Online Transportation - Winanti, Winanti; Fernando, Erick (Universitas Airlangga, 2024)
Background: The widespread use of financial technology (FinTech) is a popular aspect across various fields, particularly in online transportation. However, the usage has led to an increase in illegal FinTech, causing significant problems for public. Issues related to account security, such as hacks leading to the loss of user balances and misuse of data, contribute to the erosion of brand image and public trust. Despite the growing prominence of FinTech, explorations on the application in the context of online transportation remain limited. Previous studies have not discussed the impact of brand image on perceived usefulness and ease of use. Therefore, this current study explores the importance of combining brand image and trust factors to increase user intention. This process is achieved by investigating brand image and trust as crucial factors influencing increased perceived ease and benefits during the integration of FinTech in online transportation services. Objective: This study aimed to measure the impact of brand image and trust factors on the adoption of FinTech in online transportation. Methods: The investigation was carried out with a quantitative analysis approach using Partial Least Squares–Structural Equation Modeling (PLS–SEM). Furthermore, it focused on understanding FinTech services in online transportation, incorporating factors such as trust, brand image, perceived ease of use, perceived usefulness, and user intention. Data were collected by using a purposive sampling method through online questionnaire distribution. PLS-SEM was adapted for analyzing variable relationships, hypotheses, and models. Results: The results showed that factors including trust, perceived ease of use, and perceived usefulness significantly influenced the willingness to use FinTech in online transportation services. However, it was observed that brand image factors did not impact user intentions. Conclusion: This study showed a critical aspect in understanding the value of FinTech services by explaining the importance of establishing trust and building a good brand image as precursors. These factors indirectly contributed to increased perceived benefits and ease of use. Therefore, the insights offered valuable input for companies aiming to develop trusted FinTech platforms with a positive product image. Keywords: Brand Image, Trust, FinTech, Online Transportation